Determination of complex amplitudes of the reference and subject the wave fields on interference patterns - Guzhov, V. I.; Ilinykh, S. P.; Emelyanov, V. A.; Marchenko, I. O. (2016 11th International Forum on Strategic Technology (IFOST), 2016)
Introduces a new methods of calculation of complex analytical and substantive reference amplitude wave fields in interferogram, obtained by the methods of phase shifts (PSI) and chance of the intensities of the interferogram (CI). The development of the proposed methods allows to establish a new direction in the analysis of interferograms.